Análise de 1ª e 2ª leis da termodinâmica em “parede solar” utilizando água e nanofluido de prata como fluidos de trabalho - Teles, Clayton Ferreira (2023)
The tendency in the near future is for fossil fuels to become a scarce source of energy as the years go by. An alternative for energy generation is renewable energy, which is not only clean but virtually inexhaustible. One of the primary sources of renewable energy is solar energy, which can be harnessed in both photovoltaic and solar thermal forms. The latter involves the use of thermal energy obtained directly from solar energy collection. To achieve this, solar collectors need to have ever-improving efficiencies to make better use of this energy. One type of solar collector is the flat plate solar collector with direct absorption, here referred to as the "Solar Wall," as it is positioned vertically. One way to enhance the performance of flat plate solar collectors with direct absorption is to improve the properties of the working fluid, which can be achieved by using nanofluids. A nanofluid that has proven to be quite efficient is silver nanofluid. In this study, the performance of a flat plate solar collector with direct absorption was evaluated by comparing the first and second law efficiencies of thermodynamics using water and silver nanofluid as working fluids. The "Solar Wall" was defined as the control volume with low-temperature fluid inlet and high-temperature fluid outlet after absorbing the captured energy. The evaluation included the calculation of solar incidence, temperature at the "Solar Wall," and, finally, the first and second law efficiencies of the apparatus. The results, with first law efficiencies increasing by approximately 25% and second law efficiencies exceeding 0.6%, are consistent with the efficiencies of flat plate thermal collectors. They also show promise for further improvement and the potential use of other working fluids.